Treatment and generation of electricity from palm oil mill effluent using locally isolated electroactive microbes in microbial fuel cell - Hassan Sh. Abdirahman Elmi, 1981-; Zaharah Ibrahim, supervisor; Fakulti Biosains dan Biokejuruteraan (2014)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2014